AVALIAÇÕES EM LARGA ESCALA: relações com o desempenho dos educandos nas avaliações nacionais. - CORREIA, Lenise Mendes (2017)
This research presents, initially, a study on educational evaluation focusing on the performance of students in the national evaluations, emphasizing SAEB and Prova Brasil, highlighting the Basic Education Development Index - IDEB, as a crucial factor for the implementation of actions of this nature and will also bring discussions about educational evaluation. The research encompasses a cutout of the metropolitan region, which has a sample of the thirteen regional education districts , eight primary schools were selected, five from the state public network, and three from the municipal public network, with the criterion being the cutout of one school by Regional Education District in the education of the São Luis Regional Unit of Education . Highlighting the schools that grow the most in performance. This study demonstrates the historical evolution of students' performances, as well as their performance during the editions of the national evaluations, which aspects contributed positively to the result in the evaluations of the state and municipal public networks of São Luís and what are the main obstacles to the students' performances. The study deals with the history of educational evaluation, from the first American and English studies, and reports on the Brazilian experience in educational tests and measures. It highlights the historical evolution of educational evaluation in the world and in Brazil, with emphasis on the history of evaluation and the measurement of tests, with reference to several scholars who study the subject in the beginning of the evaluation. The research perform this historical survey of the evaluation, with the intention to understand the first indications about the educational evaluation, its historicity, in order to extend knowledge about the students on the subject of measurement, of tests, of the docimology, with a view to reflect on measurement and the current national evaluations with repercussions for the learning of the students of the Brazilian public school. The study makes a detailed analysis of the evaluation model and the large-scale evaluations of all the pedagogical nuances related to the students' performances and also raises questions about the challenges of this model in the teaching networks. The empirical research carried out has as a locus two elementary schools of the state system belonging to the metropolitan region of São Luís; and has as subjects the teachers and managers of the selected schools. The research brings an interesting clipping about student performance in the external evaluations with emphasis on effective schools, school effect, with details about military schools and their performances as successful experience of the state and municipal teaching network.